Neurofibroma of the bile duct: a rare cause of cholestatic jaundice that mimics Klatskin’s tumor - Gómez-Rázuri, Katherine (2021)
The neurofibroma of the bile duct is an extremely rare and generally asymptomatic disease, however, it maybe cause obstructive jaundice and mimic a Klatskin tumor, leading to radical surgical treatment and increased patient morbidity. We present the case of a 62-year-old woman who underwent cholecystectomy 10 years ago, with jaundice and pain in the right upper quadrant, as well as auxiliary tests compatible with cholestasis. Dilation of the bile duct and the presence of a tumor in the left hepatic duct were observed by magnetic cholangioresonance. The preoperative clinical diagnosis was hilar cholangiocarcinoma, but the histopathological study revealed a neoplasm composed of spindle cells without atypia or mitotic activity, whose neurogenic lineage supported by its positivity to protein S100 in immunohistochemistry. We report the case given its infrequency in the literature and its relevance, as it is a benign entity, as a differential diagnosis of cancer.